2009
DOI: 10.3748/wjg.15.5287
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal bacterial microflora and mucus layer thickness inadolescents with inflammatory bowel disease

Abstract: AIM:To assess the mucosa-associated bacterial microflora and mucus layer in adolescents with inflammatory bowel disease (IBD). METHODS:Sixty-one adolescents (mean age 15 years, SD ± 4.13) were included in the study. Intestinal biopsies from inflamed and non-inflamed mucosa of IBD patients and from controls with functional abdominal pain were cultured under aerobic and anaerobic conditions. The number of microbes belonging to the same group was calculated per weight of collected tissue. The mucus thickness in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 37 publications
2
78
2
2
Order By: Relevance
“…In addition, the mean numbers of culturable bifidobacteria were also lower in both UC and CD patients than in the control children, which is in agreement with previous studies. 14,41,44,46 Moreover, the diversity of bifidobacterial populations, as detected with bif-DGGE, was higher in the control children than in the UC and CD patients [p < 0.05 for all control vs disease groups]. Gevers et al 45 found that the imbalance in the microbial community was only observed in the microbiome profiles obtained from tissue samples, and was not seen in the fecal samples collected at the time of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mean numbers of culturable bifidobacteria were also lower in both UC and CD patients than in the control children, which is in agreement with previous studies. 14,41,44,46 Moreover, the diversity of bifidobacterial populations, as detected with bif-DGGE, was higher in the control children than in the UC and CD patients [p < 0.05 for all control vs disease groups]. Gevers et al 45 found that the imbalance in the microbial community was only observed in the microbiome profiles obtained from tissue samples, and was not seen in the fecal samples collected at the time of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidences have shown that in a pathological intestine, the thickness of the mucus layer is reduced, resulting in a closer contact between bacteria in the intestinal lumen and the intestinal epithelium, which may induce inflammatory processes in the bowel (Fyderek et al, 2009). In our study, no changes between the thickness of the mucus layer of the control and treatment groups were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis in the intestinal microbiota of persons with IBD has been described, but there are still varied reports on changes in the abundance of Bifidobacterium and Lactobacillus organisms in patients with IBD. We have shown that, among others, the numbers of Bifidobacteria are low in children with early, acute UC [15]. Wang [16] concluded recently that Bifidobacteria and Lactobacilli are increased in patients with active IBD after application of probiotics.…”
Section: Discussionmentioning
confidence: 68%